Evaluation Of The Relationship Of Kinesiophobia With Anxiety, Upper Extremity Disability And Quality Of Life In Patients With Frozen Shoulders - Batmaz, Oznur Uysal; Yakar, Burkay; Mirzaoglu, Tacettin; Yilmaz, Ahmet; Em, Serda; Batmaz, Ibrahim (Georg Thieme Verlag Kg, 2024)
Introduction Frozen shoulder is a painful shoulder disease in which glenohumeral joint movements are actively and passively restricted in all directions. If not treated, it can cause various psychological diseases and muscle and joint diseases. Kinesiophobia; this is defined as a fear of physical activity resulting from excessive sensitivity and an uncomfortable feeling due to painful or repeated injury. In this study, it was aimed to evaluate the relationship of kinesiophobia to upper extremity disability, anxiety and quality of life in patients with frozen shoulder.Materials and methods Firat University Faculty of Medicine, Department of Physical Medicine and Rehabilitation, between September 2020 and March 2021; As a result of clinical evaluation and radiological examinations, patients were enrolled between the ages of 18-75 and who agreed to participate in the study; 48 patients were diagnosed with frozen shoulder and met the inclusion and exclusion criteria of the study and were included in the patient group; Fourty healthy subjects aged between 18-75 years, who did not have shoulder disease and who met the inclusion and exclusion criteria of the study, were included in the control group. A total of 88 cases were included in the study. The following scales were used. TAMPA kinesiophobia scale to assess kinesiophobia in patients and control group, Beck Anxiety scale to assess anxiety in patient group; The Disabilities of The Arm, Shoulder and Hand (DASH) scale to assess upper extremity disability; Short Form (SF)-36 was used to assess quality of life.Results TAMPA kinesiophobia scale was found to be significantly different in the patient group when the patient group and control group were compared. According to the correlation analysis, the TAMPA kinesiophobia scale showed a positive correlation with the Beck-Anxiety and DASH scales in the patient group, while a negative correlation was found with the SF36-Physical function, emotional role difficulty and social functionality.Conclusion In patients with frozen shoulder, kinesiophobia seems to be associated with increased anxiety and upper extremity disability, as well as low quality of life. Structural disorders as well as psychological factors should be taken into account among the reasons for the prolonged limitation of movement and delayed recovery. When the physicians serving in the primary care are experienced with patient management with frozen shoulder, as evaluated for therapeutic purposes, planning psychological support treatments in addition to medical and physical therapy will increase the quality of health care provided to patients.
Bewertung des Zusammenhangs von Kinesiophobie mit Angstzuständen, Behinderung der oberen Extremitäten und Lebensqualität bei Patienten mit Frozen Shoulders
Keywords: frozen shoulder; kinesiophobia; anxiety; disability; quality of life